PENGARUH MODAL SOSIAL TERHADAP PENINGKATAN KINERJA INTERNAL PEGAWAI PEMERINTAH DI KANTOR KECAMATAN PURI KABUPATEN MOJOKERTO - Fauzia, Nurul; Muhaimin, Hikmah; Wijaya, Dian (Universitas Islam Majapahit, Indonesia, 2022)
This research aims to describe the influence of social capital on the level of performance of Puri District Office employees. Social capitalin this case, it is capital that occurs both in individuals, groups and organizations in building social interactionsIn it, a sense of trust is built to carry out mutually beneficial cooperation to develop individuals, groups and othersorganization. The theory used in this research is Robert D Putnam's theory regarding social capital which has elements of social networks, trustand the norms contained therein. And this research method is quantitative research using a case study approach with typesassociative research. This research uses Pearson product moment correlation analysis techniques with validity, reliability and normality tests. And resultThis research is about the influence between social capital and increasing the performance of government employees in Puri District. The greater the social capitalobtained, the performance of government employees at the Puri District Office will also increase